The Influence of Nutrition and Health Intervention Program Coverage on Stunting Prevalence Achievement in South Central Timor Regency - Tahun, R.A. Karolina; Picauly, Intje (Pergizi Pangan DPD NTT, 2025)
Background: The prevalence of stunting in NTT was 37.9% in 2023 and decreased slightly to 37% in 2024. This remains above the Indonesian health cut-off (10%) and WHO's threshold (20%). The NTT government continues its prevention and mitigation efforts to accelerate stunting reduction. Objectives: This study aims to analyze the effect of nutrition and health intervention program coverage on stunting prevalence in South Central Timor Regency. Methods: This qualitative study used secondary data for the 2024 period in TTS Regency. Data from the e-PPGBM application included intervention program coverage (Exclusive Breastfeeding and MP-ASI) and health program coverage (Complete Immunization, Defecation, Clean Water Availability, and Basic Sanitation). The dependent variable was stunting prevalence in the region. Logistic regression was used to test the influence of the program coverage on stunting prevalence. Results: The analysis found that exclusive breastfeeding coverage (0.048 < 0.05) and the proportion of families who stopped open defecation (0.045 < 0.05) significantly influenced stunting reduction in the area. Conclusions: Accelerating stunting reduction can be achieved by promoting exclusive breastfeeding for six months and encouraging clean and healthy living behaviors, particularly the cessation of open defecation.